Laparoscopic thermoablation of colorectal cancer metastases to the liver – new experience of the centre - Murawa, Dawid; Spychała, Arkadiusz; Lewandowski, Adam; Nowaczyk, Piotr (Contemporary Oncology/Współczesna Onkologia, 2012)
Aim of the study : Thermoablation of metastatic lesions in the liver is very commonplace. At present there are 3 essential techniques of access to carry out the procedure: open surgery, percutaneous technique and laparoscopic method. Percutaneous thermoablation is criticised due to the possible lack of radicalism. On the other hand, thermoablation during open surgery is a big perioperative trauma for the patient. The laparoscopic technique seems to be a compromise between the aforementioned techniques. The aim of this study was to present the technique and preliminary results of thermoablation of the liver carried out by means of the laparoscopic technique. Material and methods : Laparoscopic thermoablation was carried out in 4 patients with colorectal cancer metastases to the liver. In order to precisely locate the tumour and guarantee radi calism of the surgery, laparoscopic probe ultrasonography was carried out during the procedure. Results : All the patients underwent the procedure without any difficulties. All the patients left the hospital department as soon as 3 or 4 days after the surgery. This was about 7 days earlier in comparison with the open surgery procedure, which had been carried out before. The patients required a supply of analgesics only during the first 48 hours – non-steroid anti-inflammatory drugs, which made a substantial difference between them and the patients treated with the open surgical technique. Thanks to the laparoscopic ultrasound technique one patient had an additional lesion located, which had not been described in preoperative examinations. Conclusions : In combination with ultrasonography, laparoscopic access, which does not have a very invasive character, seems to be relatively simple and effective to carry out the procedure of thermoablation.